EKSISTENSI CALON TUNGGAL DALAM PEMILIHAN KEPALA DAERAH PASCA PUTUSAN MAHKAMAH KONSTITUSI - Lia Nurhasanah (Program Studi Hukum Tata Negara, Institut Agama Islam Negeri Parepare, 2023)
The background of this research is the inability to overcome the problems that have arisen after the Constitutional Court Decision Number 100/PUU-XII/2015. The reason is, this decision raises many problems, especially regarding the rise of single candidates that have emerged. The purpose of this research is to find out the implications of the Constitutional Court's decision Number 100/PUU-XIII/2015 for regional elections. This study uses normative juridical research methods using primary and secondary legal materials. The data collection used was library researchwhichwas conducted on various data that has relevance to the implications of the Constitutional Court decision Number 100/PUU-XIII/2015 on the local elections. This study uses a statutory approach (statute approach), and a conceptual approach (conceptual approach). The results of this study indicate that das sein and das sollen are not in sync, because after the decision it only creates new phenomena which are considered to undermine democratic values. Even so, in reality in PKPU the implementation of single candidate and empty box regional elections does have rules. However, there is no certainty regarding the regulation regarding the mechanism for holding regional elections with a single candidate if the problems in it are deadlocked.